Direct and indirect relations between family conflict and youth's later behavioral outcomes. Issue 2 (3rd October 2020) - Streit, Cara; Carlo, Gustavo; Ispa, Jean M.; Palermo, Francisco
Abstract: The present study examined the associations between family conflict during toddlerhood and children's prosocial and aggressive behaviors approximately 9 years later, as well as whether maternal supportiveness and children's self‐regulation mediate those associations. Family conflict has been identified as a risk factor for children's well‐being and behavioral problems. However, these studies often are confined to conflict during childhood, and few studies have considered the long‐term effects of conflict in toddlerhood on outcomes in late childhood. Participants were 2, 215 mothers and their children (49.3% female) from the Early Head Start Research and Evaluation Project. Families were followed from 15 months to fifth grade. Findings demonstrated direct effects of family conflict on children's aggressive behaviors and indirect effects (via maternal supportiveness) of family conflict on youth's prosocial behaviors. The present study highlights the possible long term, deleterious effects of family conflict on parenting, children's self‐regulatory skills, and social behaviors.